Influencing factor of crushable sand soil on liquefaction - Tharushini, Thiagarajan (2017)
Liquefaction resistance of sand is highly influenced by the characteristics of soil itself. Sand particle crushing or breakage occur when there is excessive stress exert on the sand soil and lead to reduction in effective stress of soil and increase in pore water pressure that result in liquefaction. In this research, the three locations in East Coast Peninsular Malaysia were chosen where the activities of crushing such as pile installation commonly occurs. When the liquefaction potential of the sand soil being affected, this will lead to the failure of construction design which was designed based on existing sand properties by neglecting the conditions of the sand after being crushed Hence, this research was conducted to identify the factor that highly influence the soil's susceptibility to liquefaction. The influencing factors that have been studied in this research are relative density and angularity. The sand soil samples from different area were collected. The samples were crushed by using automatic compactor for 500 and 1000 blows. After the crushing process, the sand samples before and after crushed were subjected to a series of test in the soil and geotechnics laboratory which are sieve analysis test, pycnometer method for specific gravity test and relative density test in order to determine the properties of soil such as, specific gravity, relative density and particle size distribution. The USB digital microscope was used to capture the soil particles in order to calculate the angularity index of the sand soil before and after crushed. The crushability of sand particle after 500 and 1000 blows was analyzed by using D5o Breakage Index. The relative density and angularity of sand samples before and after crushed were studied according to the D5o Breakage Index in order to find out the relationship between influencing factor of crushable soil and liquefaction potential. Based on the result obtained, it is clearly significant that angularity of crushable sand is highly influencing liquefaction.